Bioinspired Functional Surfaces Enabled by Multiscale Stereolithography. Issue 5 (12th February 2019) - Li, Yuanrui; Mao, Huachao; Hu, Pan; Hermes, Mark; Lim, Haneol; Yoon, Jongseung; Luhar, Mitul; Chen, Yong; Wu, Wei
Abstract: Additive manufacturing has many advantages in creating highly complex customized structures. In this study, a low‐cost multiscale stereolithography technology that can print a macroscale object with microscale surface structures with high throughput is demonstrated. The developed multiscale stereolithography is realized by dynamic switching of laser spot size and adaptively sliced layer thickness. An optical filter based on subwavelength resonance grating is used to modify laser spot size for lasers with different wavelengths and achieves a maximum resolution of 37 µm. The multiscale stereolithography process has 4.4× throughput improvement compared with the traditional stereolithography process with a single laser spot. For proof‐of‐concept testing, artificial shark skins with microriblet features are designed and 3D printed. In pipe flow experiments, the 3D printed shark skin demonstrates almost 10% average fluid drag reduction. Artificial lotus leaf surfaces are also 3D printed to demonstrate superhydrophobic property. This new process has the potential to serve as a powerful tool that can bring bioinspired structures into real‐life applications. Abstract : A multiscale stereolithography technology that is capable of high printing resolution and high throughput is demonstrated. It is realized by dynamic laser spot size switching and adaptive printing layer thickness. Many biomimetic structures that are multiscale and difficult to manufacture with existing 3D printing technologies can now be fabricated. For demonstration, artificial shark skin and lotus leaf are printed.